If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = -11x + 12 Reorder the terms: 9 + 7x = -11x + 12 Reorder the terms: 9 + 7x = 12 + -11x Solving 9 + 7x = 12 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. 9 + 7x + 11x = 12 + -11x + 11x Combine like terms: 7x + 11x = 18x 9 + 18x = 12 + -11x + 11x Combine like terms: -11x + 11x = 0 9 + 18x = 12 + 0 9 + 18x = 12 Add '-9' to each side of the equation. 9 + -9 + 18x = 12 + -9 Combine like terms: 9 + -9 = 0 0 + 18x = 12 + -9 18x = 12 + -9 Combine like terms: 12 + -9 = 3 18x = 3 Divide each side by '18'. x = 0.1666666667 Simplifying x = 0.1666666667
| 7x+9and=-11x+12 | | -(9q+7)+3(2q-5)= | | 8y-2=14y-3 | | 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 |